Distance learning courses in developing future music teachers’ instrumental performance competence - Liudmyla H. Havrilova; Olena Ye. Ishutina; Valentyna V. Zamorotska; Darja A. Kassim (CTE Workshop Proceedings, 2019)
The scientific and methodological background of creation and development of the distance learning courses for the future music teachers is substantiated. The components and structure of future music teachers’ instrumental performance competence are defined; the content of the course is revealed. The materials are based on the authors’ teaching experience within the distance learning course “Basic Musical Instrument (Piano)”. The main blocks of the distance course design and development are considered among them to be theoretical, practical, individual work, and control blocks. The specificity of distance learning methods in the future music teachers’ instrumental and performance training is substantiated and three main methods are distinguished. The method of involving information and communication technologies, including multimedia; project method, and features of knowledge and skills controlling are elaborated. The results of implementation and experimental research of using distance learning courses for developing future music teachers’ instrumental performance competence are described. The influence of different methods use on students’ success is explored.